Crisis Magazine as a Diffusive Platform of Latin American Literary Culture in the Seventies (Palimpsesto, 2020)
Crisis magazine can be considered as a true diffusive platform of Latin American literary culture in the sixties when setting trends of authors, painters, intellectuals, works of our continent. In that sense, this magazine tried to put into discussion all the Latin American literary culture often emerging in the cultural field of Latin America. This work attempts to account for these processes of dissemination, transmission and reflection of Latin American literary culture within the pages of the first period of Crisis magazine.
Keywords: Crisis; Latin American literature Culture; Cultural Magazine